Trend in the developments of the electric vehicles (EV) and policy towards its implementation: consumers’ needs - Lim, Pei Xuan. (2012)
This project endeavours to investigate the trend in the developments of Electric Vehicles (EVs) in Singapore. In addition, it also aims to analyse how suitable the relevant policies are, with reference to the consumers’ needs.